Hepatic manifestations of drug reaction with eosinophilia and systemic symptoms syndrome - Maria Gabriela Delgado; Stefania Casu; Matteo Montani; Felix Brunner; Nasser Semmo; Annalisa Berzigotti; Jean François Dufour (Exploration of Medicine, 2021)
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a potentially life-threatening drug reaction, which can affect multiple organs. Patients with DRESS syndrome and hepatic manifestations may present alterations ranging from mild hepatitis to acute liver failure. The diagnosis might be difficult, and the management of these patients is challenging. This report analyzes a series of five cases reporting the clinical presentation, which ranged from acute hepatitis to liver failure, and discussed their treatment.